United Nations E-Government Survey 2016 - United Nations Department of Economic; Social Affairs (United Nations, 2017)
Since 2001, the United Nations Department of Economic and Social Affairs (DESA), Division for Public Administration and Development Management (DPADM) has published the United Nations E-Government Survey (“the Survey”). Now in its ninth edition, the Survey provides an analysis of emerging public administration trends and issues and of how e-government can support the realization of the internationally agreed development agenda and goals. The Survey offers insights about common challenges, broad trends and different strategies in e-government development among regions and across countries. By tracking the progress of countries globally over time, the Survey seeks to better understand the challenges and opportunities that the Member States face in developing their e-government programmes.